Challenges for food waste reduction campaigns: requirements for Asian consumers in Australia. Issue 4 (2nd October 2022) - Kansal, Monika; Mitsis, Ann; Ananda, Jayanath; Pearson, David
ABSTRACT: Conserving natural resources has socio-cultural underpinnings. Food is a fundamental natural resource, and its waste at the household level has received significant attention across the globe. Food waste reduction campaigns are a prominent way to bring social change to minimise food waste. This study explores the influence of food waste reduction campaigns from a cultural perspective. Specifically, it examines the effects of food waste reduction campaigns organised by a state government agency and a major supermarket chain on three South Asian communities (Indian, Bangladesh and Sri Lankan) living in Australia. Using data from 90 participants in nine focus groups, we found that cultural-religious backgrounds of the specific Asian communities significantly impact their food behaviour. These three communities share cultural similarities about frugality, food insecurity, and religion. In some instances, consumers from all three communities felt excluded from the food waste minimisation campaigns due to unfamiliar campaign faces, western menus, and inappropriate messages and moral appeal. To make food waste reduction campaigns more effective, the principles of social marketing must be employed in campaign design. It is also crucial that the target communities trust the campaign sponsors. Campaign communications could also benefit from a cultural-religious based consumer market segmentation e.g. by customising the campaign messages to include culture-specific emotional and moral appeals.